(untitled) - Jagelcak, Juraj (Doprava a spoje, 2012)
Transport of steel coils is one of the specialized transport, for which is usually used a maximum payload of the vehicle combination. For this reason it is important to spread the coils trough the semi-trailer otherwise there is a danger of the tractor or trailer bogie overloading. Several manufacturers of semi-trailers offer extended triple-axle trailer where legislation can allow 27 tons load per triple-axle versus 24 tons of standard use.Extended triple-axle makes sense especially for vehicle combinations with a gross combination weight of 42-45 tons, hence its use in Slovakia is not possible in terms of higher payload. In the Czech Republic it is possible to use the two-axle tractors to the total weight of 45 tons and three-axle tractor unit to the total weight of 48 tons.The triple-axle partially helps load distribution where it is possible to move the load to the rear but this is limited by the minimum load required for the coupling to the tractor because of transmission of traction forces and the advantage is more likely to occur again in the total gross combination weight over 40 tons.